The Effectiveness of Kahoot! as an Assessment Media in English Lesson - Sofyan Firmansyah, Muchammad; Alfian, Mohammad; Arif Romadhon, Syaefani (Jurnal Bahasa Inggris, 2019)
Entering the 4.0 industrial revolution, many electronic-based learning media occur to make the learning process becomes more colorful compared to the one-way learning process. Game-based learning is one of the new media that occurs nowadays. Kahoot! is one of the popular game-based learning media that is popularly played in the class. However, the effectiveness of Kahoot!as an assessment media of English lesson is rarely conducted. In this research, the simple linear regression is used as the method. Furthermore, SPSS was used to check the validity and reliability of the questions given to the respondents. Even though there were 65 respondents, the questionnaires could be collected only 39 questionnaires. From the statistic test, the value of t is 5.405 > t table which is 1,998 made H0 is rejected. According to the statistic analysis, it can be concluded that the effectiveness of Kahoot! as an assessment media is only 30%. Some of the respondents argue that it is not very effective especially while showing the rank of the participants.